ART Prospektif Monitoring Terhadap Kejadian Dispensing Error pada Total Parenteral Nutrition (TPN) di NICU Gedung Bougenville RSUP Fatmawati pada Periode Bulan April 2026 dengan Analisa Kajian Farmakoekonomi - Nisrina Rafifah (RSUP Fatmawati, 2026)
Total Parenteral Nutrition (TPN) is an essential therapy for neonates in the Neonatal Intensive Care Unit (NICU) with complex clinical conditions and a high risk of medication errors, requiring strict monitoring, particularly during the dispensing process. This study aimed to evaluate TPN distribution patterns based on the five rights principle and to analyze pharmacoeconomic aspects in patients at the NICU of Bougenville Building, RSUP Fatmawati. This study used a descriptive observational design with a prospective approach conducted during April 2026, involving 10 neonatal patients with a total of 66 observations. Data were collected through direct observation of the dispensing process, review of prescriptions and medical records, and brief interviews with the responsible pharmacist. Evaluation was carried out on the accuracy of right patient, right drug, right dose, right route, and right infusion rate, as well as direct cost analysis including drugs, medical devices, and personal protective equipment. The results showed that all parameters of the five rights principle achieved 100% compliance with no medication errors identified. The total cost of TPN therapy was IDR 2,342,425 with an average cost per patient of IDR 232,856, indicating cost variation influenced by individual clinical conditions. From a pharmacoeconomic perspective, the TPN dispensing system was considered effective and efficient as it achieved optimal clinical outcomes with controlled costs. In conclusion, TPN distribution in the NICU of Bougenville Building, RSUP Fatmawati has met patient safety standards and demonstrated efficiency in resource utilization.